2021
DOI: 10.1007/s41669-021-00302-6
|View full text |Cite
|
Sign up to set email alerts
|

Time Trade-Off Utilities for Hereditary Angioedema Health and Caregiver States

Abstract: Background Hereditary angioedema (HAE) is an inherited chronic rare disease characterised by recurrent swelling attacks that are associated with significant physical and psychological burden. There is limited understanding of the effect of attack location on this burden and of caregiver burden. Objective Our objective was to capture the relative burden of HAE health and caregiver states, including different attack locations, through a time trade-off (TTO) analysis involving participants from the general public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(69 reference statements)
1
1
0
Order By: Relevance
“…Furthermore, studies from China 53 and Denmark 85 showed that QoL was even lower in patients with a recent HAE attack. This is in line with markedly higher burden of HAE during an HAE attack versus attack‐free state as estimated by time trade‐off utility values reported in a study from the United Kingdom 88 . Therefore, better disease control and corresponding reduction in the number or frequency of HAE attacks may increase QoL, as shown in studies from China 53 and Germany 89 .…”
Section: Methodssupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, studies from China 53 and Denmark 85 showed that QoL was even lower in patients with a recent HAE attack. This is in line with markedly higher burden of HAE during an HAE attack versus attack‐free state as estimated by time trade‐off utility values reported in a study from the United Kingdom 88 . Therefore, better disease control and corresponding reduction in the number or frequency of HAE attacks may increase QoL, as shown in studies from China 53 and Germany 89 .…”
Section: Methodssupporting
confidence: 79%
“…This is in line with markedly higher burden of HAE during an HAE attack versus attack‐free state as estimated by time trade‐off utility values reported in a study from the United Kingdom. 88 Therefore, better disease control and corresponding reduction in the number or frequency of HAE attacks may increase QoL, as shown in studies from China 53 and Germany. 89 It should, however, be noted that patients with HAE experience QoL impairment between HAE attacks, as well as during an attack: they report ongoing fear of another attack, and disease interference with education and career.…”
Section: Methodsmentioning
confidence: 99%